A Critical Discourse Analysis: Reconceptualising Online Distance Learning through a Foucauldian lens - Lee, Kyungmee; Brett, Clare (Proceedings of the International Conference on Networked Learning, 2014)
There is a lot of rhetoric related to current internet based distance education as accessible, flexible, just-in-time, cost-effective, innovative and interactive. In particular, discussion about the value of interaction for successful online learning experiences, which is grounded in social constructivist learning theories, has been ongoing for recent decades. The burgeoning popularity of online learning such as a MOOCs phenomenon and the rapid proliferation of its new name “e-learning” have pushed aside the older connotation of distance learning as an inferior form of learning compared to face-to-face instruction. With the advent of web technologies and the growing public interest in the Internet, a simultaneous claim from internet-based research that such environments are inherently interactive has reinforced the rhetoric about the “interactive nature of online learning”. As a result, literature suggests researchers have single-mindedly focussed on developing more effective interactive online learning with neither empirical examination of the claims nor careful investigation of distance educational contexts where their designs would be implemented in. In this context, the changing roles of online teachers have drawn great research attention and so have been conceptualized and theorised. This Foucauldian critical discourse analysis project looks closely into the rhetorical discourse and their influences on instructors’ perspectives and behaviours at open universities to address the gap in our current understanding about distance education. Two foci of this study are i) instructors’ language use: how instructors at open universities talk about their perspectives and experiences of online learning and ii) instructors’ subjects: how each instructor is described and characterized by other members at the universities and why. We conducted semi-structured interviews with 17 instructors in two open universities, one in North America and the other in Asia-Pacific region. Our findings show the powerful impact of the rhetorical discourse on instructors’ perspectives and their subjects, which has increased the potential danger of the institutional abuse of power against or the marginalization of a particular group of instructors. The ultimate aim of this study is not to refute social constructivist assumptions but to provide a different framework to broaden our understanding of the nature of online learning beyond the current set of assumptions.